SPIRAL COMPUTED TOMOGRAPHY IN DIAGNOSTICS OF COMPL ICATIONS OF ACUTE PANCREATITIS - T. G. Barmina; F. A.-K. Sharifullin; O. A. Zabavskaya; P. A. Ivanov (Неотложная медицинская помощь, 2016)
BACKGROUND. Early detection of complications of pancreatic necrosis including purulent-septic ones largely predetermines the outcome of the treatment. In this article, we evaluated the role and capabilities of X-ray computed tomography in the diagnosis of acute pancreatitis complications.OBJECTIVE. Studying the capabilities of spiral computed tomography (SCT) in the diagnosis of acute severe pancreatitis complications.MATERIAL AND METHODS. Spiral CT results in 56 patients with severe acute pancreatitis and suspected septic complications have been analyzed.RESULTS. Revealed complications of the severe acute pancreatitis: circumscribed collection of fluid (32), abscesses of bursa omentalis and retroperitoneal fat (18), retroperitoneal phlegmon (6). The semiotics of revealed complications has been described, and their relation with other organs and structures has been evaluated.CONCLUSIONS. SCT conducted with contrasting techniques, reveals septic complications of severe acute pancreatitis, ascertains their form, location and amount, as well as the relation with other organs and structures which helps identify the tactics of management, indications for surgery and assess its effectiveness.